2010
DOI: 10.1021/la103009a
|View full text |Cite
|
Sign up to set email alerts
|

Free-Standing and Reactive Thin Films Fabricated by Covalent Layer-by-Layer Assembly and Subsequent Lift-Off of Azlactone-Containing Polymer Multilayers

Abstract: We report an approach to the fabrication of freestanding and amine-reactive thin films that is based on the reactive layer-by-layer assembly and subsequent lift-off of azlactone-containing polymer multilayers. We demonstrate that covalently crosslinked multilayers fabricated using the azlactone-functionalized polymer poly(2-vinyl-4,4-dimethylazlactone) (PVDMA) and a primary amine-containing polymer [poly(ethyleneimine) (PEI)] can be delaminated from planar glass and silicon surfaces by immersion in mildly acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
62
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(63 citation statements)
references
References 55 publications
(197 reference statements)
0
62
1
Order By: Relevance
“…We have described in several recent reports a ‘reactive’ layer-by-layer approach25 to the assembly of covalently crosslinked multilayered films that exploits the versatile reactivity of azlactone-functionalized polymers 2630. Polymers bearing azlactone functionality, such as poly(2-vinyl-4,4-dimethylazlactone) (PVDMA, Eq.…”
Section: Introductionmentioning
confidence: 99%
“…We have described in several recent reports a ‘reactive’ layer-by-layer approach25 to the assembly of covalently crosslinked multilayered films that exploits the versatile reactivity of azlactone-functionalized polymers 2630. Polymers bearing azlactone functionality, such as poly(2-vinyl-4,4-dimethylazlactone) (PVDMA, Eq.…”
Section: Introductionmentioning
confidence: 99%
“…16,23 For films treated with decylamine, the peak corresponding to the azlactone functionality at 1819 cm -1 was completely consumed, suggesting exhaustive reaction of the azlactone groups with the incoming amine-based nucleophile and consistent with the results of past studies. 16,23,25 For films treated with decanol, the intensity of the azlactone carbonyl stretch at 1819 cm -1 was nearly fully consumed, and a carbonyl C=O stretch at 1724 cm -1 appeared, consistent with the formation of ester bonds upon the ring-opening of the azlactone groups with this alcohol-based nucleophile. Finally, for films treated with decanethiol, the azlactone peak was also consumed and close inspection of the data reveals a shoulder on the amide C=O stretch (near 1652 cm -1 ) that we attribute to the C=O carbonyl stretching of thioester functionality.…”
Section: Modification Of Interfacial Properties Using Alcohol-and Thimentioning
confidence: 96%
“…Subsequent work demonstrated the versatility of this azlactone-based approach as a means to coat and modify the interfacial properties of a variety of different materials and more complex substrates, including the surfaces of glass [54][55][56][57][58][59][60]143], soft materials (e.g., polymer-based substrates) [59,61], paper [62], cotton thread and commercial wound dressings (Figure 15.12e,f) [62], protein-based surfaces (e.g., horsehair) [62], inorganic microparticles (for the fabrication of hollow microcapsules Figure 15.12g,h) [63], and, owing to the ability to perform covalent assembly in organic solvents that are immiscible with water, liquid/liquid interfaces formed between organic and aqueous phases (for the fabrication of suspended membranes; Figure 15.12i) [64]. In each of these studies, the presence of amine-reactive azlactone functionality on the surface (or within the bulk) of the films provided a convenient and straightforward platform for further postfabrication modification of surface properties by exposure to a broad range of different amine-functionalized molecules (including amine-functionalized small molecules [54,55,[57][58][59][60][61][62][63], proteins [55,61], peptides [65], functional polymers [61], and amine-functionalized droplets of thermotropic liquid crystals [56]).…”
Section: Reactive Lbl Assembly Using Azlactone-functionalized Polymersmentioning
confidence: 99%
“…Buck et al [57] demonstrated that PEI/PVDMA films fabricated on untreated (nonsilanized) silicon substrates could be induced to delaminate and lift off to yield cross-linked, stable, and amine-reactive freestanding thin films (Figure 15.12j) that can be postfunctionalized and physically transferred onto the surfaces of other objects. Other examples of this approach using other reactive polymers are discussed in the following section.…”
Section: Reactive Lbl Assembly Using Azlactone-functionalized Polymersmentioning
confidence: 99%